Legal Pathways for Environmental Justice for Indigenous Communities in Indonesia (Indonesian Minority Justice Review, 2025)
This paper explores the legal pathways through which indigenous communities in Indonesia can achieve environmental justice in the face of land dispossession, deforestation, and the encroachment of large-scale development projects. Indonesia’s indigenous populations often face direct threats to their traditional territories due to economic development, logging, and mining activities, which are exacerbated by weak legal protections and inadequate enforcement of environmental laws. The study examines the relevant legal frameworks, including the 1999 Forestry Law, the 2001 Law on Cultural Rights, and the 2012 Indigenous Peoples’ Rights Recognition Bill, which address environmental justice issues for indigenous communities. Through a combination of case studies and legal analysis, the paper highlights both successful and failed attempts at leveraging the legal system for environmental justice, focusing on the role of the courts, local governments, and advocacy groups in protecting indigenous land rights. The findings suggest that while legal reforms in recent years have increased recognition of indigenous land rights, implementation remains inconsistent, and communities continue to face severe environmental degradation. The paper concludes by proposing enhanced legal pathways for environmental justice, such as more robust enforcement mechanisms, stronger recognition of customary land rights, and better representation of indigenous communities in environmental policymaking.